Economic Analysis of Jobs Investment Projects - Robalino, David A. (The World Bank, 2017)
This Note systematizes the economic evaluation of Jobs Investment Projects. It explains the limitations of past approaches that have regarded jobs only as a by-product of growth. It focuses on market failures that create a gap between the social and private return on investments and reduce the number of good jobs below the socially optimal level. Two of these market failures are: labor externalities arising from the divergence between the market price and opportunity cost of labor; and social jobs externalities linked to improved jobs outcomes for groups such as youth, women, and the extreme poor. These externalities can amplify other market failures such as learning spillovers and coordination failures. The analysis is integrated within a Cost-Benefit framework, to facilitate decision making around jobs investment programs. The Note discusses applications to different sorts of projects: those that focus on improving the labor supply and labor market matches; those that focus on strengthening firms' demand for labor; and integrated projects, that include both types of interventions